PENGARUH ETOS KERJA, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT HADJI KALLA DI MAKASSAR - Muhammad Bakri (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this study is 1) to analyze the influence of work ethic on employee performance at PT. Hadji Kalla in Makassar, 2) to analyze the influence of competence on employee performance at PT. Hadji Kalla in Makassar and 3) to analyze the effect of work environment on employee performance at PT. Hadji Kalla in Makassar. The method of analysis used in this research is Multiple Regression analysis method. Research data obtained from employees of PT. Hadji Kalla in Makassar. The research approach is a causal approach that is explanatory. The results of this study indicate that: 1) employees of PT. Hadji Kalla in Makassar has a high work ethic that has a positive impact on employee performance, 2) employees of PT. Hadji Kalla in Makassar has a high competence so as to have a positive impact on employee performance, and 3) the better the working environment PT. Hadji Kalla in Makassar, the better the performance of employees.